Injuries after falls at work in the United Kingdom and Sweden with special reference to fractures in women over 45. Issue 11 (November 1997) - McNamee, R; Kemmlert, K; Lundholm, L; Cherry, N M
Abstract : OBJECTIVES: To describe the relation with age of risk of reported injury after a fall among women at work in two countries, the United Kingdom and Sweden, with particular emphasis on fractures, and to interpret these data. METHODS: Rates of accidents compiled under the national reporting regulations of each country during a two year period were described by age, sex, cause (fall on the level, fall from a height, other), and occurrence of fracture, with emphasis on the relative risk (RR) in workers aged 45 years and over compared with those aged under 45. For fractures (major fractures only in the United Kingdom) among women, RRs were calculated for all occupations, with the three digit occupational classification schemes of each country. Summary RRs for older versus younger women, directly standardised for occupation, were derived. RESULTS: Among women, RRs for injury after a fall on the level and fall from a height were 2.77 and 1.77 respectively in Sweden and 2.28 and 1.54 in the United Kingdom. When restricted to fractures, the RRs became 4.75 and 3.66 respectively in Sweden and 3.35 and 1.97 in the United Kingdom. Standardisation for occupation gave RRs for fractures of 4.87 and 3.75 in Sweden and 3.43 and 2.16 in the United Kingdom. Almost all occupational groups with enough fractures for analysis showed an excess of fractures related to falls among older women. A different age pattern was seen for all injuries or fracture after other types of accidents and for all types of accident in men. CONCLUSION: It is argued that, for fractures at least, the results for women are unlikely to be due to reporting bias and unlikely to be explained by a greater exposure to workplace hazards among older women. Whether there is an increased risk of falling, as distinct from sustaining a fracture, is not clear. The generality of the increased risk suggest that efforts should be made to minimise hazards in all occupational sectors, particularly those using many women.